2020
DOI: 10.1021/acs.jafc.0c02130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Differentially Expressed Proteins Induced by Alteration of Natural Se Uptake with Ultrahigh-Performance Liquid Chromatography Quadrupole Orbitrap Uncovers the Potential Nutritional Value in Se-Enriched Green Tea

Abstract: Se-enriched green tea, with an increasing consumption, is the shoot of tea plants grown naturally in a seleniferous region. A label-free proteomic strategy based on ultrahigh-performance liquid chromatography quadrupole Orbitrap was applied to characterize and distinguish the difference between the Se-enriched and normal green tea with a total of 283 proteins identified and 264 proteins quantified, in which 96 proteins were observed different. The expressions of 10 proteins were upregulated and 40 proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…In the current investigation, the application of Se enrichment resulted in a significant elevation of secondary metabolites, specifically terpenoids and alkaloids. Jia, Liu, Shi, & Chu (2020) have demonstrated that Se enrichment could remarkably promote the synthesis of some secondary metabolites in plants, as revealed by the KEGG pathway analysis in this study. That is, the changed secondary metabolites were attributed to the metabolic pathways and biosynthesis of secondary metabolites.…”
Section: Discussionsupporting
confidence: 62%
“…In the current investigation, the application of Se enrichment resulted in a significant elevation of secondary metabolites, specifically terpenoids and alkaloids. Jia, Liu, Shi, & Chu (2020) have demonstrated that Se enrichment could remarkably promote the synthesis of some secondary metabolites in plants, as revealed by the KEGG pathway analysis in this study. That is, the changed secondary metabolites were attributed to the metabolic pathways and biosynthesis of secondary metabolites.…”
Section: Discussionsupporting
confidence: 62%
“…Multi-omics technologies have been implemented in studies related to selenium disposition in many other plants. However, single omics method was usually applied toward this particular research in tea plants ( Cao et al, 2018 ; Jia et al, 2020 ). In this study, both transcriptome and proteome techniques were applied to explore the transcriptional and post-transcriptional changes in tea plants after treated with selenite and selenate, respectively, illustrating the primary mechanism of selenium disposition in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins and flavonols share a metabolic pathway for flavonoid synthesis, with naringenin being catalyzed by flavonoid 3-hydroxylase (F3H) to produce dihydrokaempferol, and flavonol synthase (FLS), flavonoid 3′5′-hydroxylase (F3′5’H), and flavonoid 3′-hydroxylase (F3′H) differentiating the biosynthesis of dihydrokaempferol into cannabinol, dihydrquercetin, and dihydromyricetin to produce the myricetin 3-glycosides, quercetin, and catechin compounds (Figure ). , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Catechins and flavonols share a metabolic pathway for flavonoid synthesis, with naringenin being catalyzed by flavonoid 3-hydroxylase (F3H) to produce dihydrokaempferol, and flavonol synthase (FLS), flavonoid 3′5′-hydroxylase (F3′5'H), and flavonoid 3′-hydroxylase (F3′H) differentiating the biosynthesis of dihydrokaempferol into cannabinol, dihydrquercetin, and dihydromyricetin to produce the myricetin 3-glycosides, quercetin, and catechin compounds (Figure 7). 1,36 Selenium content can affect catechin levels in tea, with (−)-catechin gallate, (−)-epigallocatechin, (−)-epigallocatechin 3-gallate, and (+)-gallocatechin being significantly decreased in 0.6 and 1.2 mg kg −1 selenium-enriched Fu tea and significantly increased in 2.4 mg kg −1 selenium-enriched Fu tea (Figure 4C). (−)-Catechin gallate and (−)-epigallocatechin 3-gallate involve two biosynthetic steps: The production of β-glucogallin from uridine diphosphate glucose and gibberellic acid, and the production of gallocatechin from 2,3-cis-flavan-3-ol and β-glucogallin, with gibberellic acid being encoded by CsUGT84A22 as the enzyme that catalyzes the conversion to β-glucogallin.…”
Section: Combining Word2vec and Hnsw Coupled With Uhplc And Tandem Ma...mentioning
confidence: 99%
See 1 more Smart Citation